Microstructural evolution in Pt-implanted polycrystalline Al2O3. (15th January 2015) - Gandman, Maria; Ridgway, Mark; Gronsky, Ronald; Glaeser, Andreas M.
Abstract: Microstructural evolution in the near-surface layer of a model metal–ceramic system, Pt-implanted high-purity polycrystalline Al2 O3 (PCA), was studied, and compared to that in Pt-implanted sapphire. Interactions between Pt particles and migrating α / α grain boundaries in PCA caused Pt particle redistribution and Pt loss, and were evaluated in the context of Zener pinning and particle-drag theories. The experimental method allows the transition from the original to the new equilibrium shape due to the changes in orientation relationship to be examined. As a result of the potentially wide range of equilibrium shapes, interface crystallographies, and transitional morphologies that the microstructural evolution imposes, the experimental method provides a flexible framework for fundamental studies of the energetic and kinetic properties of ceramic–metal interfaces.